Analysis of Occupational Safety and Health Risk in the Private Hospital Laboratory - Siregar, Rani Deviani; Mudayana, Ahmad Ahid (International Journal of Healthcare Research, 2024)
Background: Hospitals are complex healthcare institutions, which provide diagnosis, treatment and rehabilitation services to individuals in need. Its main focus is on patient safety and risk management, including occupational safety and Health. Occupational safety and health measures aim to protect workers and visitors from potential accidents in the workplace. Clinical laboratories in hospitals are one of the areas with the highest OHS risks, which have a key role in creating a safe environment for both patients and workers. This study aims to understand laboratory activities, identify hazards and risks, assess risks, evaluate risks, and provide risk control recommendations. Methods: This study used qualitative methods with in-depth interview techniques and observation using HIRARC form sheets. The research design used was a case study approach. Interview informants were selected through snowball sampling technique. Results: The results of the study are in accordance with the AS/NZS 4360: 2004 standard on the HIRARC form to conduct risk assessments on microbiology, clinical chemistry and immunology, hematology, and hospital blood bank service activities. This risk assessment is used to provide risk control recommendations, which are based on the Occupational Health Safety Administration's OHS risk control hierarchy. The most dominant risk controls carried out are engineering controls and the use of personal protective equipment (PPE). Conclusion: OHS risk analysis in the laboratory activities of PKU Muhammadiyah Yogyakarta Hospital shows satisfactory results, but still requires increased compliance in the use of PPE, updating laboratory SOPs, as well as monitoring and rearranging workspace and environmental cleanliness.